A visible‐light‐excited fluorescence method for imaging protein crystals without added dyes. (1st February 2016) - Lukk, Tiit; Gillilan, Richard E.; Szebenyi, Doletha M. E.; Zipfel, Warren R.
Abstract : Protein crystals exhibit temperature‐dependent autofluorescence when excited with visible light. The intensity of visible‐light‐excited autofluorescence is tenfold higher at cryogenic temperatures owing to temperature‐dependent chromophore stabilization. Abstract : Fluorescence microscopy methods have seen an increase in popularity in recent years for detecting protein crystals in screening trays. The fluorescence‐based crystal detection methods have thus far relied on intrinsic UV‐inducible tryptophan fluorescence, nonlinear optics or fluorescence in the visible light range dependent on crystals soaked with fluorescent dyes. In this paper data are presented on a novel visible‐light‐inducible autofluorescence arising from protein crystals as a result of general stabilization of conjugated double‐bond systems and increased charge delocalization due to crystal packing. The visible‐light‐inducible autofluorescence serves as a complementary method to bright‐field microscopy in beamline applications where accurate crystal centering about the rotation axis is essential. Owing to temperature‐dependent chromophore stabilization, protein crystals exhibit tenfold higher fluorescence intensity at cryogenic temperatures, making the method ideal for experiments where crystals are cooled to 100 K with a cryostream. In addition to the non‐damaging excitation wavelength and low laser power required for imaging, the method can also serve a useful role for differentiating protein crystals from salt crystals in screening trays.